2008
DOI: 10.1097/qad.0b013e32830184df
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis in a clinical cohort of HIV-1-infected patients

Abstract: Early neurosyphilis was common in this cohort. Highly active antiretroviral therapy to reverse immunosuppression may help mitigate neurological complications of syphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
2
23

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 17 publications
7
141
2
23
Order By: Relevance
“…It was not surprising that this patient did not show much improvement in symptoms following treatment. Findings from a previous study (Ghanem KG et al, 2008) showed that in 38% of patients, the major symptom persisted after 1 year and 29% needed retreatment. However, some cases had documented improvement of psychotic symptoms after penicillin therapy (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…It was not surprising that this patient did not show much improvement in symptoms following treatment. Findings from a previous study (Ghanem KG et al, 2008) showed that in 38% of patients, the major symptom persisted after 1 year and 29% needed retreatment. However, some cases had documented improvement of psychotic symptoms after penicillin therapy (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…On Reibergrams, this can be seen to be connected with intrathecal production of specific antibodies (IgG quotient), which would indicate local activity, while the IgG index itself might have less sensitivity in this regard 12,13,14,15,16 . These diagnostic alternatives have made it possible to obtain information in cases of symptomatic HIV-negative patients.…”
mentioning
confidence: 99%
“…Numerous prior studies have shown that the risk of neurosyphilis in HIV-infected patients with systemic syphilis is significantly higher in the setting of neurological symptoms such as headache or ocular symptoms. 24,30,31 Additionally, reduced peripheral blood CD4+ T-cell count has been associated with the risk of neurosyphilis: CD4 T-cell counts of 350 uL -1 in several studies 24,31,32 and 500 uL -1 in a more recent study 30 have been clearly associated with an increased probability of neurosyphilis in HIV-infected persons, as defined by CSF criteria. Some controversy remains as to whether high serum rapid plasma reagin (RPR) titres also predict neurosyphilis.…”
Section: Laboratory Definitions Of Neurosyphilismentioning
confidence: 99%
“…15,16,33 The rates of syphilis reported by Marra et al, Leber et al and Ghanem et al in individuals undergoing lumbar puncture based on these criteria ranged from 20 to 27%. 24,30,32,34 Importantly, HIV-infected patients with syphilis who are virally suppressed on combination ART may be at lower risk of neurosyphilis compared with those not taking combination ART. 32 Two retrospective studies have suggested that uncontrolled plasma HIV RNA (>50 copies mL ) increased the risk of neurosyphilis.…”
Section: Laboratory Definitions Of Neurosyphilismentioning
confidence: 99%
See 1 more Smart Citation